Bolečine v križu pri operacijskih medicinskih sestrah - Fortuna, Tatjana (Obzornik zdravstvene nege, 2003)
The article presents the frequency of low back pain in perioperative nurses working in the Operational Theatre of the Hospital Center in Ljubljana. The first part describes causes of low back pain and the possibilities of its prevention. The second, empirical part describes and presents the results of aresearch study on the frequency of the occurence of low back pain in perioperative nurses. The results show that 77% of the nurses have experiencedlow back pain once or several times, that 75% are familiar with themethods of prevention while only 42% also apply them at work.
Keywords: ankete; bolečina; Diagnosis; hrbtenica; Križ, bolečina; Low Back Pain; medicinske sestre; Occupational Exposure; Operacijska soba, nega; Operating Room Nursing; Poklicna izpostavljenost; preprečevanje; Prevention And Control; Questionnaires